Zbiory przybliżone z relacją dominacji dla wielokryterialnego problemu klasyfikacji państw Unii Europejskiej pod względem poziomu rozwoju gospodarczego - Gruszka, Iwona (The Rough Sets Approach Based on Dominance Relation to Multicriteria Classification of EU Countries by Economic Development, 2007)
The rough sets approach based on dominance relation was introduced by Greco, Matarazzo and Słowiński. The dominance relation permits to describe the approximations of the a priori known decision classes. On the base of the approximations the decision model is induced. The decision model contains the decision rules of "if ... then ..." terms. This model permits to describe by an nonparametric way what is certain, uncertain or even impossible in the data base. Furthermore the model is easy to interpret and permits to support the classification process of new objects. The approach is used to multi-criteria EU countries classification problem by economic development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 578-586